The United Nations council for Namibia with special emphasis on its Decree No 1 - Bruggemann, Jur Bernd (Global Risk Governance Programme, 2021)
This thesis examines the legal status of the United Nations Council for Namibia and the validity of its actions before and after the independence of the Territory with special emphasis on its Decree No 1. Chapter I describes the natural environment of Namibia, its human resources and economic conditions. These are basic to the interpretation and evaluation of the policies concerning administration and development of the Territory. The problem of Namibia in the UN is analysed in Chapter II. All organs of the Organisation, the GA, the SC, and the ICJ found that South Africa's presence in Namibia was illegal and that South Africa had no right to administer the Territory. As a result the UN terminated South Africa's Mandate over Namibia and established the UNCfN (as a subsidiary organ of the GA irt terms of art 22 of the Charter). This body then administered the Territory until its independence in March 1990. Because UNCfN was a unique institution in the history of the Organisation, and because of the Council's uncertain legal status, Chapter IV examines the legal character of the Council and concludes that UNCfN had legitimate powers over the Territory (even with regard to foreign affairs). In its capacity as administering authority, UNCfN, on 27 September 1974, issued Decree No 1 for the protection of the natural resources of Namibia. The legal force of this Decree in international law before and after independence is the focus of discussion in Chapter V. With regard of the validity of this Decree before independence, an examination of the practice of states shows that almost all Member States of the UN denied the Decree binding force in international law. To hold otherwise would imply that the Council could create international legal obligations for UN Members, thereby giving the Council greater powers than those of a sovereign government. Because the Decree is an act of the Namibian Government (following its incorporation into the Namibian Constitution), the validity of Decree No 1 after independence is discussed in terms of the principles governing observance of foreign acts of state. The finding is that other states are free to recognise paras 1 and 3 (as self-executing acts) or execute paras 4 and 5 (as nonself-executing acts). The observance of para 2 of _the Decree as an illegal act of state in international law depends on the approach of the state concerned to the act of state doctrine. Continental states adhere to territorial principle, and so they usually deny the validity of illegal foreign acts, whereas Anglo-American jurisdictions refuse to examine foreign acts in terms of their compliance with international law. Because of the confusion surrounding the judicial use and proper scope of the doctrine, however, one can only speculate that an American might observe para 2 of the Decree.